Islam, Perbedaan dan Kesetaraan Gender - Agus Hermanto (Nizham Jurnal Studi Keislaman, 2017)
Islam is a revelation to the Prophet Muhammad as a way of life in this world and hereafter, the religious mission is to liberate man from forms of anarchy and injustice, tolerance is an attitude of respect for others, in terms of cause and roots, there are two forms of difference, namely; 1) the difference tang caused by factors morals, arise because of the character is known by scholars and murabbi (builder) that takes into account various motivations of the various attitudes and events, 2) differences caused by factors in mind, arising from different points of view about a problem , either natural or problems amaliah problem. Al-Qur'an is basically the principle of justice, equality, democracy and social well do, if then occurs an injustice, it is not happening in Islam, but it may be precisely the interpretation of Islam itself weak, causing a lot of understanding.